Anthroponomastic of Parish of Bieliny in the Light of Parish Books of the Years 1850–1900 - Sikora, Ewa (Respectus Philologicus, 2017)
The aim of the present article is onomastic analysis of male surnames reported in the documents of the parish of St. Joseph Spouse of the Blessed Virgin Mary in Bieliny (built in 1637), derived from the second half of the 19th century. The analysis encompass five hundred sixty-four surnames. The classification of surnames was based on the division of surnames proposed by Stanislaw Rospond. He divided the surnames into derivative and non-derivative ones. The most productive group of derivative surnames was formed by the use of different suffixes. Among them, the most numerous are surnames with the suffix -ski, derived from place-names and first names. Among non-derivative surnames there prevail appellative surnames related with the names of professions, physical characteristics and personality, as well as surnames associated with nature, foods, abstractions, homemade production, substance and minerals, places and clothes. These names feature lexical differences.
Keywords: surnames; onomastic classification; motivation